1972
DOI: 10.1177/00220345720510060601
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Degradation of Amalgam Restorations

Abstract: Amalgam restorations in contact with saliva and tissue fluid act as concentration cells. The galvanic current is associated with selective attack of the γ 2 phase and loss of mechanical properties. Tin is deposited in the underlying dentin. Cavity liners do not stop the degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Corroded phases in or near the indentations may be more easily deformed during compression of the diamond indentor than uncorroded phases. MATEER & REITZ (17) have also reported that the Knoop hardness of corroded portions of amalgam restorations was lower than that of uncorroded regions.…”
Section: Discussionmentioning
confidence: 96%
“…Corroded phases in or near the indentations may be more easily deformed during compression of the diamond indentor than uncorroded phases. MATEER & REITZ (17) have also reported that the Knoop hardness of corroded portions of amalgam restorations was lower than that of uncorroded regions.…”
Section: Discussionmentioning
confidence: 96%
“…Over a period of time corrosion progresses from interfaces toward the center of the restoration, reducing hardness and embrittling the matrix structure by molecular disintegration of the γ 2 phase. 14,21,29,31,37 Chloride ions in saliva, food and drinks play an essential role in the corrosion process and the deposition of metallic salts.…”
Section: Corrosion Products Of Dental Amalgammentioning
confidence: 99%
“…Typically Sn was the element that was 6 found in dentin in all dentin penetration studies. 9,[18][19][20][21][22][23][24][25] Mateer and Reitz 21 detected low Hg and Ag content in blackened dentin, but the Sn content in dentin adjacent to amalgam was about as …”
mentioning
confidence: 97%
“…In conventional dental amalgams the corrosion process may cause the y2-phase to decompose more or less completely with time [Jorgensen, 1967;Mateer and Reitz, 1972;Holland and Asgar, 1974], The cor rosion combined with a high porosity level in the amalgam [Schoch and Loebich, 1955;Jorgensen et al, 1966] may allow fluoride ions to leach also from the inner parts of a fluoride-containing amalgam and to react with the surrounding tooth substance [Min oguchi et al, 1967;Forsten et al, 1976]. In vitro studies indicate an increased rate of corrosion after the addition of stannous fluoride to the alloy [Stoner et al, 1971;Hurst and von Fraunhofer, 1978].…”
mentioning
confidence: 99%